Reaction time estimation based on recursive short-term principal component analysis for skeletal information of badminton players - Sagawa, K.; Shishido, H.; Suita, M.; Kitahara, I. (Proceedings of the 11th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2023)
The aim of this paper is to measure the shot-reaction intervals of badminton players based on time-series 3D skeletal information. In competitions where game dominance changes, effective plays and tactics in situations can be investigated by analyzing the measured reaction intervals. In our proposed method, we estimated shot-reaction intervals using a badminton player`s motion information and applied a short-term principal component analysis to the sequential 3D skeletal information of athletes to extract features useful for motion analysis. Hit and reaction times were detected by identifying the extrema in the first and second principal component scores. We estimated a shot`s reaction interval from the hit time to the reaction time at which the player starts moving in response. We applied the proposed method to the 3D skeletal information of a badminton player and confirmed that reaction intervals can be estimated. By using the results of this study to provide feedback to badminton players on the analysis of reaction intervals, players can learn and improve their effective and ineffective tactics and plays.